Drug Related Problems (DRPs) Terapi Antibiotik pada Pasien Sepsis di Bangsal Rawat Inap Rumah Sakit X di Surakarta - Maliza, Fera Nor; Gonibala, Alfiana Pramasita (Universitas Nurul Jadid, 2025)
Sepsis is a systemic response to infection that can lead to organ damage and death. Inappropriate use of antibiotics is associated with prolonged hospitalisation and increases the risk of death in sepsis patients. Sepsis leads to high mortality, inappropriate antibiotic use worsens outcomes. This study was an observational study using a cross sectional design. Data collection was done prospectively through searching medical records of sepsis patients aged ≥18 years who were being treated in the inpatient ward of Hospital X in Surakarta. DRPs analysis was conducted based on the PCNE 2017 version 8.02 classification. Data were further analysed using Chi- Square to determine the association of risk factors with the incidence of DRPs. Antibiotic use consisted of empirical and definitive antibiotics with a total of 93 empirical antibiotic uses and 26 definitive antibiotic uses. The majority of empirical antibiotic use was ampicillin-sulbactam (62.36%), a combination of ampicillin-sulbactam with levofloxacin (20.43%), and the majority of definitive antibiotic use was meropenem (21.73%). DRPs problems in this study were 63.02% (75 cases) of 119 cases of antibiotic use with the most DRPs problems in the effectiveness of therapy in 52.09% of cases of antibiotic use. The risk factors studied (age, gender, length of hospitalisation, number of drugs and comorbidities) are not relate to incidence of drug related problems (P> 0.05).